Fatigue reliability assessment considering traffic flow variation based on weigh-in-motion data. Issue 1 (January 2017) - Zhang, Jing; Au, FTK
The remaining service life of a bridge is an important criterion for the bridge master to make decisions of maintenance and rehabilitation. In the assessment of fatigue problems of steel and composite bridges, a crucial step is to determine the fatigue stress spectra, which are usually obtained through field measurements. In this study, the standard fatigue vehicle spectrum of Ting Kau Bridge in Hong Kong is obtained from the dynamic weigh-in-motion system that monitors the traffic flow and volume and axle and gross vehicle weights. An advanced probabilistic loading model is proposed to simulate the vehicles running along the bridge based on measurements from the weigh-in-motion system considering not only the diurnal variations of traffic flow within different time intervals but also the rate of change of the annual traffic. The statistical fatigue reliability assessment at critical locations can then be carried out to estimate the remaining service life of the bridge.